Terrestrial and Meteorite Carbon Appear to Have the Same Isotopic Composition - Libby, W. F. (1971)
The carbon-isotope ratio recently obtained for the carbon found in the Murchison meteorite, which has been shown (by the racemic nature of twelve component amino acids) to be free of terrestrial contamination, agrees with that for average terrestrial sediments. This finding indicates that the earth and the stony meteorites contain carbon of the same isotopic composition.